Embryonic stem cells overexpressing high molecular weight FGF2 isoform enhance recovery of pre-ganglionic spinal root lesion in combination with fibrin biopolymer mediated root repair - Lima, B. H.M.; Cartarozzi, L. P.; Kyrylenko, S.; Ferreira, R. S. [UNESP]; Barraviera, B. [UNESP]; Oliveira, Alexandre L. R. (My University, 2024)
Background: Spinal ventral root avulsion results in massive motoneuron degeneration with poor prognosis and high costs. In this study, we compared different isoforms of basic fibroblast growth factor 2 (FGF2), overexpressed in stably transfected Human embryonic stem cells (hESCs), following motor root avulsion and repair with a heterologous fibrin biopolymer (HFB). Methods: In the present work, hESCs bioengineered to overexpress 18, 23, and 31 kD isoforms of FGF2, were used in combination with reimplantation of the avulsed roots using HFB. Statistical analysis was conducted using GraphPad Prism software with one-way or two-way ANOVA, followed by Tukey’s or Dunnett’s multiple comparison tests. Significance was set at *p < 0.05, **p < 0.01, ***p < 0.001, and ****p < 0.0001. Results: For the first set of experiments, rats underwent avulsion of the ventral roots with local administration of HFB and engraftment of hESCs expressing the above-mentioned FGF2 isoforms. Analysis of motoneuron survival, glial reaction, and synaptic coverage, two weeks after the lesion, indicated that therapy with hESCs overexpressing 31 kD FGF2 was the most effective. Consequently, the second set of experiments was performed with that isoform, so that ventral root avulsion was followed by direct spinal cord reimplantation. Motoneuron survival, glial reaction, synaptic coverage, and gene expression were analyzed 2 weeks post-lesion; while the functional recovery was evaluated by the walking track test and von Frey test for 12 weeks. We showed that engraftment of hESCs led to significant neuroprotection, coupled with immunomodulation, attenuation of astrogliosis, and preservation of inputs to the rescued motoneurons. Behaviorally, the 31 kD FGF2 - hESC therapy enhanced both motor and sensory recovery. Conclusion: Transgenic hESCs were an effective delivery platform for neurotrophic factors, rescuing axotomized motoneurons and modulating glial response after proximal spinal cord root injury, while the 31 kD isoform of FGF2 showed superior regenerative properties over other isoforms in addition to the significant functional recovery.
Keywords: Cell therapy; Embryonic stem cells; Fibroblast growth factor 2; Motoneurons; Spinal cord injury